PENGARUH ORIENTASI BELANJA, E-TRUST, DAN E-SERVICE QUALITY TERHADAP MINAT BELI DI LAZADA - Dionisius Dominikus Daud Carvallo; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The porpose of this study was to determine the effect of Shopping Orientation (XI), E-Trust (X2), and E-Service Quality (X3) on Purchase Interest (Y) in Lazada. This type of research is quantitative research. The population in this study were active students in Yogyakarta with a total of 120 samples. Sampling was done by using purposive sampling method. The data collection technique used is a survey method using a questionnaire. Then the data was processed using SPSS IBM Version 25, the data analysis techniques used were data quality test, classical assumption test, multiple regression test, t test, and coefficient of determination. Based on the results of this study, shopping orientation has a positive and significant effect on buying interest. This is evidenced by the t-count value of 3.021 and the significant value 0.003<0.05. E-Trust has a positive and significant effect on buying interest, this is evidenced by the t-count value of 2.039 and the significant value shown is 0,039<0.05. E-Service Quality has a positive and significant effect on buying interest, this is evidenced by the t-count value of 4.229 and the significant value shown is 0.000<0.05.